1998
DOI: 10.1007/s002590050274
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of technetium-99m sestamibi uptake in multiple myeloma

Abstract: Technetium-99m 2-methoxyisobutylisonitrile (99mTc-MIBI) has been proposed as a potential tracer in patients with multiple myeloma (MM). The aims of this study were to evaluate the incidence of various patterns of diffuse 99mTc-MIBI uptake in patients with MM, to assess their relationship with clinical status and stage of disease, and to try to clarify the meaning of the diffuse bone marrow uptake of 99mTc-MIBI. Thirty-nine consecutive patients with MM were studied. Twenty-nine of these patients had active dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 10 publications
3
40
1
Order By: Relevance
“…The meaning of 18 F-FDG diffuse bone marrow uptake in MM patients must be further investigated, as a mild and diffuse 18 F-FDG uptake in the spine could be also found in young or mildly anemic patients (28,29). On the other hand, previous studies showed that 99m Tc-MIBI concentrates in malignant plasma cells and that diffuse tracer uptake correlates with the percentage of plasma cell infiltration and the amount of a monoclonal component (13,15). Moreover, it has been shown that 99m Tc-MIBI bone marrow uptake is able to identify active myeloma and that the extension and intensity of tracer uptake correlates both with the clinical status and the stage of disease (13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The meaning of 18 F-FDG diffuse bone marrow uptake in MM patients must be further investigated, as a mild and diffuse 18 F-FDG uptake in the spine could be also found in young or mildly anemic patients (28,29). On the other hand, previous studies showed that 99m Tc-MIBI concentrates in malignant plasma cells and that diffuse tracer uptake correlates with the percentage of plasma cell infiltration and the amount of a monoclonal component (13,15). Moreover, it has been shown that 99m Tc-MIBI bone marrow uptake is able to identify active myeloma and that the extension and intensity of tracer uptake correlates both with the clinical status and the stage of disease (13).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous studies showed that 99m Tc-MIBI concentrates in malignant plasma cells and that diffuse tracer uptake correlates with the percentage of plasma cell infiltration and the amount of a monoclonal component (13,15). Moreover, it has been shown that 99m Tc-MIBI bone marrow uptake is able to identify active myeloma and that the extension and intensity of tracer uptake correlates both with the clinical status and the stage of disease (13). In fact, a previous study showed that moderateto-intense diffuse 99m Tc-MIBI uptake or focal uptake with or without diffuse uptake, in the absence of inflammation or other pathologies, excludes the diagnosis of monoclonal gammopathy of unknown significance (MGUS) and correlates with poor prognosis (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tc99m MDP is less sensitive than X-ray in detecting skeletal lesions in patients with MM as it is not capable of evaluating bone marrow disease activity owing to lack of osteoblastic response usually produced in bone 3 . Tc99m Both Tc99m MIBI and Tc99m (V) DMSA have been reported as tumor imaging agents for many neoplasm and bone metastases including multiple myeloma [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%